A Theoretical Study of 2-nitrofuran vs 3-nitrofuran as Dienophilic Electrophile in Polar Cycloaddition Reaction: Comparison of the Reactivity and Reaction Mechanism - Cainelli, Mauro (2016)
In this study, we analyzed in a theoretical form the behavior of 2-nitrofuran and 3-nitrofuran acting as dienophilic electrophiles in polar cycloaddition reactions joint to different dienes. The reactivity and regioselectivity was discussed employing global and local reactivity indexes, respectively. The reaction mechanisms of these cycloadditions were compared through the transition state structures and energies calculated.